TOO WEAK TO INFLUENCE? A CASE STUDY OF THE LITHUANIAN NGDOs IN FOREIGN AID POLICY MAKING - Gadeikienė, Marta (Politologija, 2017)
For the East Central European Countries (ECE), the membership in the European Union also meant an entry into the foreign aid donor community. To understand the international development policy change in over a decade and a policy divergence among the ECE countries that have started from relatively similar situations, this article offers the case study of Lithuania and the analysis of domestic policy actors, namely the non-governmental development organizations (NGDOs) as one of the policy change facilitating factors. It provides an empirically-rich account of how Lithuanian NGDOs participate in the national foreign aid policymaking and explains factors that affect Lithuanian NGDOs’ capacity to influence government decisions. Szent-Ivanyi’s and Lightfoot’s theoretical model guided the analysis of the Lithuanian NGDOs umbrella organisations composition and power relations, their organizational capacities, foreign donor assistance and attitudes of the state actors. The article concludes the limited, yet increasing Lithuanian NGDOs’ role in shaping Lithuanian foreign aid policies, as undermined as they are by the chronic lack of resources to fund advocacy from national sources and the dependency on the EU project-based funding. Consequently, these circumstances constrain the NGDO Platforms’ focus mostly on the EU development agenda and therefore mimic the European NGO networks’ policy agenda. The lack of capacities among the NGDOs to adapt a European policy agenda to the national foreign aid policy reality makes it of limited relevance to the policy makers domestically.